Dust-enshrouded star formation at high redshift - Scott, Susan (The University of Edinburgh, 2003)
Since the advent of SCUBA, deep submillimetre surveys have succeeded in re- solving the bulk of the far -infared extragalactic background into discrete sources, revealing a population of high -redshift (z > 1) heavily dust -enshrouded massive - starforming galaxies.

Here, the nature of the most luminous 850 pm sources (S850 > 5 mJy) are considered, in particular their link with the formation and evolution of the most massive elliptical galaxies visible in the present -day Universe.

The "SCUBA 8 mJy Survey" is the largest of the blank field submillimetre surveys completed to date, designed specifically with the aim of identifying the brightest 850μm sources. It covers 260 square arcminutes of sky to a depth of Qrms ^- 2.5 mJy /beam, evenly split between two areas of low galactic cirrus emission; the Lockman Hole East and ELAIS N2. The data have in part been reduced by the standard JCMT SURF procedures, but the primary reduction method was an alternative IDL -based pipeline which has the advantage of pro- ducing uncorrelated noise images. This latter approach has enabled me to de- velop a maximum -likelihood source extraction algorithm which simultaneously measures the statistical significance of every peak in a SCUBA map, leading to properly quantified errors on the flux densities of all potential sources. Applying the source extraction algorithm to these two fields has revealed 19 sources with S/N > 4.00, 40 sources with S/N > 3.50, and 85 sources with S/N > 3.00. Completeness, mean output vs. input flux density, and contamination from spurious / confused sources were quantified using extensive Monte Carlo simulations. Using deep 1.4 GHz imaging of the survey fields to determine the radio -to- submillimetre spectral indices for every 850μm detection, all sources were constrained to lie at z > 1, with a median redshift zmed 2.4. This being the case, the inferred star formation rates are ti 1000 Mo yr -1, sufficient to form the most massive elliptical galaxies on timescales of 1 Gyr, but heavily obscured by 108 - 109 Mo of dust. The comoving number density of high redshift galaxies forming stars at > 1000 M® yr-1 is 10 -5 Mpc -3, with only a weak dependence on the precise redshift distribution, also corresponding to the number density of massive ellipticals with L > 3 - 4L* in the present -day Universe, as well as the co- moving number density of comparably massive, passively -evolving objects in the redshift band 1 < z < 2 inferred from recent surveys of extremely red objects. This suggests that the bright submillimetre sources uncovered by this survey can plausibly account for the formation of all present -day massive spheroids.

Combining the data from the "SCUBA 8 mJy Survey" with other existing blank field surveys, re- reduced and analysed in an identical manner, approximately doubles the area of sky observed with SCUBA in an unbiased manner. The full source catalogue derived from combining these fields contains a sufficient number of significant detections to place meaningful constraints on the cluster- ing properties of the bright submillimetre population. Measurements of angular correlation functions and nearest neighbour statistics for S850 > 5, 6, and 7 mJy sources, imply strong clustering on scales of ti 1 arcminute at a significance level of ti 4a. The combined datasets also allow the determination of the most accu- rate source counts to date for S850 > 2 mJy. For 2 < S850 < 8 mJy the differential source counts follow a power -law such that dN(> S) /dS oc S -1'5, but appear to steepen thereafter, possibly indicative of a high -mass cutoff. Reasonably successful modelling of the number counts can be achieved by strong pure luminosity evolution with redshift, of the local 850 pm luminosity function.